Outcome of Stapedotomy in the Treatment of Otosclerosis in a Tertiary Care Hospital: A Retrospective Study - Aria Masoom, Abdul Manan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Otosclerosis is a major ear disorder that causes conductive hearing loss. Proper treatment is crucial to prevent hearing loss. Objective: The objective of this study was to determine the outcome of stapedotomy in the treatment of otosclerosis in a tertiary care hospital Material and Method: This retrospective study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from April 2023 to September 2023 after taking approval from the research committee of the institute. We obtained and examined the clinical records of otosclerosis individuals who had done stapedotomy at the ENT department. A total of 55 Individuals diagnosed with otosclerosis and evaluated on the basis of tone audiogram and tympanometry were included. Pure tone audiometry was performed for each individual just before surgery, on the first day following the procedure, and three months later during the post-operative follow-up. Data on the comparison of the air bone gap (ABG) frequencies 0.5, 1, 3, and 4 KHz before and after surgery has been collected. The difference in pre- and post-operative (at three months' follow-up) ABG was used to compute the postoperative hearing gain. The resulting increase in hearing thresholds was categorized as best (>30dB), better (21-30dB), good (11-20dB), and fair (0-10dB) for the purposes of the analysis. Results: In the present study a total of 55 individuals were enrolled out of which 31(56%) were male and 24(44%) were female and the age ranged from 18-46 years. It was observed that thirty of the participants (54.4%) had hearing improvements of greater than 30 dB (best), whereas 12 (21.8%), eight recipients (14.5%), and 5 patients (9%) had improvements of 21–30 dB (better), 11–20 dB (good), and 0–10 dB (fair) respectively. Although all the participants presented some improvement, nobody experienced a drop in their hearing. Individuals under 35 years old had a significant improvement in their hearing thresholds when compared to those over 35 (value of p equal to 0.013). Nevertheless, the statistical evaluation revealed that the participants' gender had no significant impact on the improvement in their hearing thresholds (value of p equal to 0.446). Conclusion: The study concluded that stapedotomy is a choice of therapy for otosclerosis, improved hearing thresholds in individuals with hearing loss. Keywords: Outcome; Stapedotomy; Treatment; Otosclerosis